2005
DOI: 10.1002/elps.200410421
|View full text |Cite
|
Sign up to set email alerts
|

Direct targeting of human plasma for matrix‐assisted laser desorption/ionization and analysis of plasma proteins by time of flight‐mass spectrometry

Abstract: A method to analyze human plasma proteins without fractionation, directly applying a plasma-matrix mixture on the target plate of a matrix-assisted laser desorption/ionization-time of flight-mass spectrometer (MALDI-TOF-MS), has been described. Peaks of ionized plasma proteins could not be detected applying a mixture of an undiluted plasma sample and a matrix solution, but they appeared when the plasma was diluted before mixing with the matrix. Tenfold diluted plasma provided well-resolved protein peaks in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…In addition to glycosylation, phosphorylation at Ser68, C-terminal truncated variants (des-Gln and des-Thr-Gln) and a cysteinylated variant has been detected in the circulation (Jin and Manabe 2005;Nelsestuen et al 2008;Zhou et al 2009). ApoA-II also forms a homodimer at Cys29 that is abundant in plasma (Gillard et al 2005;Jin and Manabe 2005). Overall, more than ten different variants of apoA-II are present in humans, but the physiological relevance of this heterogeneity is unclear.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to glycosylation, phosphorylation at Ser68, C-terminal truncated variants (des-Gln and des-Thr-Gln) and a cysteinylated variant has been detected in the circulation (Jin and Manabe 2005;Nelsestuen et al 2008;Zhou et al 2009). ApoA-II also forms a homodimer at Cys29 that is abundant in plasma (Gillard et al 2005;Jin and Manabe 2005). Overall, more than ten different variants of apoA-II are present in humans, but the physiological relevance of this heterogeneity is unclear.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%
“…An early report showed that glycosylation is not necessary for apoC-III secretion and does not affect its relative affinity to different lipoprotein particles (Roghani and Zannis 1988), and, as judged by gel electrophoresis and MS analysis of HDL and plasma, the non-sialylated variant is least abundant, usually less than 5 % of total apoC-III in normal individuals (Wopereis et al 2003;Bruneel et al 2008;Mazur et al 2010;Holleboom et al 2011). In addition to glycosylation, apoC-III can also be C-terminal truncated (des-Ala and des-Ala-Ala), which further increases the number of isoforms (Bondarenko et al 1999;Jin and Manabe 2005;Nicolardi et al 2013a). Interestingly, novel results strongly suggest that glycosylation of apoC-III is an important event in the regulation of lipid metabolism (Holleboom et al 2011;Baenziger 2012).…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%
“…Heterogeneity is observed for many components because of exopeptidase action on the peptide chain, sequence variations, and variable modifications of free sulfhydryl groups of unpaired cysteines (19,20,28,(65)(66)(67). In polypeptides with unpaired cysteine residues, such as subunits of transthyretin, apolipoprotein A-II, ␣ 1 -proteinase inhibitor, and albumin, disulfides may form with a variety of compounds, such as cysteine, cysteinylglycine, glutathione, or other polypeptides (dimerization of apolipoprotein A-II), or the sulfhydryl may undergo oxidation (19,20,28,(65)(66)(67). Proteins with unpaired cysteines also may link via disulfides to other proteins, as in the case of ␣ 1 -microglobulin, such that a mixture of different covalently bound forms of the protein is observed (68 ).…”
Section: Mass Assignments Of Plasma Componentsmentioning
confidence: 99%
“…A reported analysis of a complex mixture of peptides bound to HDLs estimated that recovered small peptides had an aggregate molar concentration one fifth that of apolipoprotein A-I (77 ), so that lipoproteins may be another significant carrier of small peptides, just as they are carriers of several small plasma proteins. Detection of small peptide components in plasma specimens has not been achieved in unfractionated plasma (20 ) or lipoproteins (77 ), indicating that, without some fractionation of plasma, detection of peptides is suppressed by the more abundant larger proteins. Strategies to increase the sensitivity of MALDI-TOF MS to detect small peptides have relied on more extensive sample fractionation.…”
Section: The Low-molecular-mass Proteome or Peptidomementioning
confidence: 99%
“…However, many of these studies are hampered by the fact that due to the low amount of proteins, samples need to be pooled. Similar to plasma, tear fluid and aqueous humor have a relatively high concentration of inorganic salts [59]. Therefore well chosen sample preparation devices for desalting, like centrifugal filters [60], dialyses, or membrane preconcentrators [61], need to be used.…”
Section: Proteomic Analysismentioning
confidence: 99%